Hubungan Antara Sustainability Reporting Terhadap Kinerja Keuangan Perusahaan Dari Sisi Liquidity Ratio - Purnomo, Bernard Chrisitian (Business Accounting Review, 2014)
In recent years the Company and stakeholders begin to realize the importance of Sustainability report as a value -added business . Sustainability Report itself is a performance report that contains financial and non - financial . This research was conducted with the aim of testing the relationship of indicators in sustainability report on the companys liquidity ratio . The dependent variable was the Liquidity Ratio which can be measured by Current Ratio, Quick Ratio, and Cash Ratio . On the other hand, the independent variable in this study was the disclosure of Sustainability report by divided into indicators of economic performance , environmental and social and measured using SRDI index . The sample was 9 companies that published Sustainability Report three consecutive years in 2009-2011 that could be accessed through the companys website and the website of National Center for Sustainability Reporting and the company that publishds the Annual Financial Statements in 2010-2012 . The independent variables measured by using a standard of disclosure index by GRI (Global Reporting Initiative). This study uses secondary data collected from the companyâs website and the Indonesia Stock Exchange.The results showed that there was a significant negative affect on the disclosure of economic performance, a significant positive affect on the environmental aspects , and the positive affect that was not significant to the Liquidity Ratio .